NILAI TAMBAH PRODUKSI KAYU LAPIS, INDAH DARI BEBERAPA PERUSAHAAN DI SUMATRA UTARA - Rachman Effendi; Suwidji Basuki (Jurnal Penelitian Hasil Hutan, 1988)
One  of  the  products   that  can  be produced   from  secondary  process  of plywood  is fancy  plywood.  The product   is usually  constructed by  overlaying  plywood   with  fancy   veneer  or  other   material  with  nice  decorative  appearance.   This process  will add extra  value to  the final product   intern of selling price as compared  with  ordinary plywood.  In this study fancy. plywood   is constructed   by  overlaying plywood  with  fancy  veneer of  jati,   mahoni  and  rengas.Added  value of fancy plywood  (from plywood)in  three ply mills in North Sumatra  amounted   to Rp.1,032,749,600 in one  year resulted  from 5141 cu.m of  plywood. The  value  is accounted   for  production  factors  with   the  following proportion: 17.73 % from depreciation   factor, 21.94 % from  labour  cost,  and  60.33  % from  profit, taxes,  and  others. The employment created  by  each factory is 48  workers  which  are  equal to 13,920  man days  per year.